Bridge Expansion Joint in Road Transition Curve: Effects Assessment on Heavy Vehicles - Paola Di Mascio (Department of Civil, Constructional and Environmental Engineering, Sapienza University of Rome, Via Eudossiana 18, 00184 Rome, Italy) (MDPI AG, 2018)
Properly-designed road surfaces provide a durable surface on which traffic can pass smoothly and safely. In fact, the main causes that determine the structural decay of the pavement and its parts are the traffic loads. These repeated actions can create undesirable unevennesses on the road surface, which induce vertical accelerations on vehicles, up to hindering contact between pavement and tire, with dangerous consequences on traffic safety. The dynamic actions transmitted by the vehicles depend on these irregularities: often, a bridge expansion joint (BEJ), introducing a necessary discontinuity between different materials, determines from the beginning a geometric irregularity in the running surface. Besides, some structural conditions could emphasize the problem (e.g., local cracking due to the settlement of the subgrade near the abutment or the discontinuity of stiffness due to the presence of different materials). When the BEJ is located in a transition curve, an inevitable vertical irregularity between road and joint can reach values of some centimeters, with serious consequences for the road safety. This paper deals with the analysis of a case study of a BEJ. Several test surveys were performed in order to fully characterize the effects on both vehicles and pavement. The three-dimensional representation of the pavement surface and the acceleration measurements on a heavy test vehicle were performed to analyze the joint behavior under traffic. Finally, a finite element model was implemented to evaluate the stress contribution on vehicle components induced by the vertical irregularities.